Climate‐induced outbreaks in high‐elevation pines are driven primarily by immigration of bark beetles from historical hosts. (3rd September 2021) - Howe, Michael; Carroll, Allan; Gratton, Claudio; Raffa, Kenneth F.
Abstract: Warming temperatures are allowing native insect herbivores to expand into regions that previously exceeded their thermal tolerance, encounter new host species, and pose significant threats to native communities. However, the dynamics of these expansions remain poorly understood, particularly in the extent to which outbreaks remain reliant on emigration from historical hosts or are driven by local reproduction within novel hosts in the expanded range. We tested these non‐mutually exclusive hypotheses using spatially explicit data on mountain pine beetle ( Dendroctonus ponderosae ), which historically undergoes intermittent outbreaks in low‐elevation lodgepole pine ( Pinus contorta ), but is now causing severe mortality in a high‐elevation endangered species, whitebark pine ( Pinus albicaulis ). We compiled data from 2000 to 2019 across British Columbia, Canada, at 1‐km 2 resolution, and analyzed spatiotemporal patterns of beetle infestations, lodgepole pine distributions, expansion into habitats dominated by whitebark pine, and the likelihood of future outbreaks in all pine communities under simulated conditions. Overall, we found strong support for the hypothesis of emigration from the historical host species continuing to be a major driver of outbreaks in the more recently accessed host. First, beetle population pressure was consistently the best predictor of infestation severity in both lodgepole and whitebark pine, and appeared to be mostly unidirectional from lodgepole to whitebark pine. Second, infestations in lodgepole pine were of a longer duration than those in whitebark pine, which appeared too brief to sustain transitions from endemic to eruptive dynamics. Furthermore, resource depletion appears to drive emigration from lodgepole pine, whereas in whitebark pine drought appears to favor establishment of immigrants although bioclimatic factors and stand structure preclude self‐sustaining outbreaks. Finally, we project that most pine in British Columbia will be at risk in the event of a new major outbreak. We describe implications for conserving and protecting whitebark pine and to other climate‐driven range expansions. Abstract : Warming temperatures are allowing native insect herbivores to expand into regions that previously exceeded their thermal tolerance, encounter new host species, and pose significant threats to native communities. However, the dynamics of these expansions remain poorly understood, particularly in the extent to which outbreaks remain reliant on emigration from historical hosts or are driven by local reproduction within novel hosts in the expanded range. We tested these non‐mutually exclusive hypotheses using spatially explicit data on mountain pine beetle infestations in British Columbia from 2000 to 2019.